Development of specific primers for Fusarium oxysporum causing damping off of Lilium formolongi - Toda, Takeshi (J Genet Eng Biotechnol, 2020)
Primers specific for the hypothetical forma specialis of Fusarium oxysporum were designed to amplify DNA from this pathogenic fungus that infects plants including lilies. The F. oxysporum sequence between the transposal elements han and hop was used for primer design. Three primer pairs designed from this region were confirmed as specific for 24 isolates of F. oxysporum pathogenic to lilies, except for one pathogenic isolates as extraordinary. No amplification was observed from F. oxysporum non-pathogenic to lily, from 12 forma specialis, and 14 fungi and oomycetes concerned with Liliaceae plants. We propose that specific primers designed from this region will be useful to detect isolates of F. oxysporum that are pathogenic to lilies.